Emulsifying properties of tribomechanically treated whey proteins - Suzana Rimac Brnčić; Marija Badanjak Sabolović; Vesna Lelas (Mljekarstvo)
Whey proteins are used in a wide range of food products because of their high nutritional value and the ability to contribute to the unique functional properties of the final products. The functional properties of whey proteins are affected not only by the whey origin, season dependent variations of protein and non-protein components amount, but also by the conditions of processes involved in their isolation, purification and modification (temperature, pH, pressure, chemicals). In this research, tribomechanical micronization (TM) was used as a technique that could be useful in modification of some functional properties of whey proteins. Therefore, two different commercial powdered whey protein isolates (WPI) were used for analysis. Surface hydrophobicity and emulsifying properties (emulsifying activity and emulsion stability) were determined before and after TM treatment. The results obtained showed increases in surface hydrophobicity of WPI after TM treatment indicating that TM could induce changes of protein conformation and increase exposure of the previously buried hydrophobic regions. Emulsions prepared with tribomechanically treated WPI showed higher emulsion activity and better emulsion stability. The results obtained suggest that TM can be useful and fast process technique for improvement of functional properties of WPI.